Enhancement of stability and skin permeation by sucrose stearate and cyclodextrins in progesterone nanoemulsions - Klang, Victoria; Matsko, Nadejda; Zimmermann, Anna-Maria; Vojnikovic, Emina; Valenta, Claudia (International journal of pharmaceutics, 2010)
Lecithin-based nanoemulsions are colloidal drug delivery systems which offer fundamental advantages in topical therapy, such as excellent skin permeation of lipophilic drugs; however, their physicochemical long-term stability is usually rather poor without the use of additional synthetic surfactants such as polysorbates. In a novel approach negatively and positively charged formulations were developed without the use of conventional synthetic surfactants. Natural substances such as sucrose esters and different cyclodextrins were additionally used as stabilising agents. Emphasis was laid on optimisation of the homogenisation process and formulation properties. The optimised formulations were tested for their potential as drug delivery systems for progesterone. Furthermore, crucial formulation parameters such as particle size and zeta potential were monitored for more than a year. In this context, the effect of the natural excipients sucrose stearate and cyclodextrins α, β and γ on in vitro skin permeation was investigated; the influence of the positive particle surface charge induced by incorporation of the cationic phytosphingosine was evaluated as well. The results showed that in particular the cyclodextrins seemed to induce fundamental changes in formulation microstructure as confirmed by cryo TEM, thus leading to remarkably increased skin permeation rates of progesterone compared to the control.